Occurrences of non-linear phenomena and vocal harshness in dog whines as indicators of stress and ageing - András Marx (Nature Portfolio, 2021)
Abstract During social interactions, acoustic parameters of tetrapods’ vocalisations reflect the emotional state of the caller. Higher levels of spectral noise and the occurrence of irregularities (non-linear phenomena NLP) might be negative arousal indicators in alarm calls, although less is known about other distress vocalisations. Family dogs experience different levels of stress during separation from their owner and may vocalise extensively. Analysing their whines can provide evidence for the relationship between arousal and NLP. We recorded 167 family dogs’ separation behaviour including vocalisations, assessed their stress level based on behaviour and tested how these, their individual features, and owner reported separation-related problems (SRP) relate to their whines’ (N = 4086) spectral noise and NLP. Dogs with SRP produced NLP whines more likely. More active dogs and dogs that tried to escape produced noisier whines. Older dogs’ whines were more harmonic than younger ones’, but they also showed a higher NLP ratio. Our results show that vocal harshness and NLP are associated with arousal in contact calls, and thus might function as stress indicators. The higher occurrence of NLP in older dogs irrespective to separation stress suggests loss in precise neural control of the larynx, and hence can be a potential ageing indicator.